La place de l’art et de la culture au sein du féminisme québécois ou Jovette Marchessault d’hier et d’aujourd’hui - Michaud, Jacinthe (International Journal of Canadian Studies, 2023)
Cet article se penche sur la place des arts et de la culture au sein du féminisme de la fin des années 1960 jusqu’au milieu des années 1980 au Québec. Il met en lumière le fait que les arts et la culture occupent des espaces à l’intérieur des mouvements politiques qui ne sont pas statiques. Au cours de la première partie de cette période, les mouvements féministes/mouvements des femmes avaient créé un nombre incalculable d’instruments culturels qu’ils ont mis au service des luttes politiques contre l’oppression et l’exploitation des femmes. À l’époque, les militantes féministes avaient la conscience que les arts et la culture constituaient des aires d’expression radicale et rebelle ; des lieux où il était possible de contester la contrainte à l’hétérosexualité, la morale des institutions religieuses ; des espaces où se discutaient les idées marxistes, anticapitalistes ou anticoloniales. Le présent article réserve une attention spéciale à la production littéraire et dramatique de Jovette Marchessault.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; approches et analyses; arts; histoire et politique; hétérosexisme; identités LGBTQIA2+; militance; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

Scholarly literature in HIV-related lesbian, gay, bisexual, and transgender studies: A bibliometric analysis - Nguyen, Tham Thi; Do, Anh Linh; Nguyen, Long Hoang; Vu, Giang Thu; Dam, Vu Anh Trong; Latkin, Carl A.; Hall, Brian J.; Ho, Cyrus S. H.; Zhang, Melvyn W. B.; Ho, Roger C. M. (Frontiers in Psychology, 2023)
Introduction: Lesbian, gay, bisexual, and transgendered (LGBT) people are marginalized and understudied. Analyzing research activity worldwide is vital to better understand their needs in confronting the HIV epidemic. This study aimed to evaluate the global literature to identify the research collaboration, content, and tendency in HIV-related issues among the LGBT populations. Methods: Peer-reviewed original articles and reviews were achieved from the Web of Science Core Collection database. Country’s collaborations and co-occurrence of most frequent terms were illustrated by VOSviewer software. The Latent Dirichlet Allocation (LDA) and the linear regression model were utilized to uncover the hidden topics and examine the research trend. Results: From 1990 to 2019, a total of 13,096 publications were found. Stigma, sexual risk behaviors and HIV testing were the major topics in the LGBT research during the study period. Among 15 topics, topics about HIV/Sexually transmitted infections (STIs) prevalence, Outcomes of HIV/AIDS care and treatment, and Opportunistic infections in HIV-positive LGBT people showed decreasing attention over years, while other topics had a slight to moderate increase. Discussion: Our study underlined the exponential growth of publications on the LGBT population in HIV research, and suggested the importance of performing regional collaborations in improving research capacity. Moreover, further research should focus on examining the manner to increase the coverage of HIV testing and treatment, as well as implement HIV-interventions with low cost and easy to scale-up.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; VIH; identités LGBTQIA2+; périodes historiques; ressource en ligne; revue de la littérature; santé; thématiques